Hernia Nukleus Pulposus Lumbal: Sebuah Laporan Kasus - Fitriyani, Fitriyani; Putri, Sezia Marina (CV. Jasa Sukses Abadi, 2024)
Lumbar herniated nucleus pulposus (HNP) is a condition where fibroblasts experience degenerative or external changes in the intervertebral disc and nucleus which can cause neurological symptoms due to compression of the dura mater or nerves. The prevalence of disc herniation is around 1 to 3% and increases with age up to age 80 years. It often occurs in men compared to women with a ratio of 2:1. Lumbar invertebral discs are complex structures that frequently experience axial loads. Due to the biomechanics of this structure and its avascular nature, lumbar disc herniation often occurs. A 65 year old woman came to the emergency room at RSAM with complaints of low back pain that radiated to the thigh, calf to the sole of the right foot, as if being pricked and getting worse since 3 weeks before entering the hospital. The patient works as a farmer and when working often carries heavy objects and the patient's working position is often bent. Denied history of falls. The patient did not complain of disturbances in BAK and defecation. From the results of the physical examination, Lasseque's test was positive on the right. A lumbosacral MRI radiological examination was carried out and the results showed multiple protruded discs in the L4-L5 and L5-S1 intervertebralis accompanied by a diffuse posterior herniated nucleus pulposus which was pressing on the anterior saccus thecalis and bilateral spinal roots. Patients are treated with medication and rehabilitation. HNP is the most common cause of lower back pain complaints in the elderly. Immediate treatment can impact the prognosis.